Manajemen Mutu Pendidikan Perguruan Tinggi Keagamaan Islam Dalam Meningkatkan Kualitas Mahasiswa - Basyar, Syaripudin (Jurnal Dewantara, 2016)
Serve as a standard of quality and excellence, so that the main elements of quality in quality management is understood as a process of certainty that there has been a specific standard and continuously strived to achieve for a product or service is superior. Thus, if the quality applied in teaching refers to the level of learning compared to the standard. An activity-quality education provision is seen when higher education are able to provide the best learning opportunities.